Exploring Interactions Between Fruit and Vegetable Production in a Greenhouse and an Anaerobic Digestion Plant—Environmental Implications - Danevad, Daniel; Carlos-Pinedo, Sandra (Frontiers in Sustainability, 2021)
Greenhouse fruit and vegetable production uses large amounts of energy and other resources, and finding ways of reducing its impact may increase sustainability. Outputs generated from solid-state anaerobic digestion (SS-AD) are suitable for use in greenhouses, which creates a need to investigate the consequences of the possible interactions between them. Connecting the fruit and vegetable production with the resource flows from an SS-AD process, e.g. biogas and digestate, could increase circularity while decreasing the total environmental impact. There are currently no studies where a comprehensive assessment of the material flows between greenhouses and SS-AD are analyzed in combination with evaluation of the environmental impact. In this study, material flow analysis is used to evaluate the effects of adding tomato related waste to the SS-AD, while also using life cycle assessment to study the environmental impact of the system, including production of tomatoes in a greenhouse and the interactions with the SS-AD. The results show that the environmental impact decreases for all evaluated impact categories as compared to a reference greenhouse that used inputs and outputs usually applied in a Swedish context. Using the tomato related waste as a feedstock for SS-AD caused a decrease of biomethane and an increase of carbon dioxide and digestate per tonne of treated waste, compared to the digestion of mainly food waste. In conclusion, interactions between a greenhouse and an SS-AD plant can lead to better environmental performance by replacing some of the fertilizer and energy required by the greenhouse.